1974
DOI: 10.1128/aem.28.5.822-830.1974
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Microbial Contamination of Fluids Associated with Hemodialysis Machines

Abstract: Studies were conducted on the microbiological quality of fluids associated with different types of dialysis systems located in six dialysis centers and 14 homes. Included were (i) single-pass systems employing either parallel flow (Kiil or Gambro) or capillary cartridge dialyzers and (ii) recirculating single-pass and batch recirculating systems using coil dialyzers. Microbiological assays were performed on the water used to prepare dialysis fluid, the concentrated dialysate, and either pre-and postdialyzer di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…For example, a small study of pyrogenic reactions (i.e., reactions characterized by the onset of chills/shaking within approximately one hour of treatment followed by a fever one to two hours after treatment, as well as hypotension, headache, and muscle ache) in a single dialysis center by demonstrated that when dialysate had bacterial counts lower than 10 2 CFU/ml, there was a 4% attack rate; however, when concentrations exceeded 10 4 CFU/ml, the attack rate for pyrogenic reactions increased to 24% (36). Additional studies and outbreak investigations demonstrated that the incoming water and final dialysis fluids should not exceed a maximum contaminant level (MCL) of 100-1000 CFU because of possible pyrogenic or septicemic complications (37,38). The limits were established by consensus as 2000 CFU/ml for the dialysate bath and one log 10 lower for water used to prepare the dialysate as a result of these findings.…”
Section: Microbial Standards and Methodsmentioning
confidence: 99%
“…For example, a small study of pyrogenic reactions (i.e., reactions characterized by the onset of chills/shaking within approximately one hour of treatment followed by a fever one to two hours after treatment, as well as hypotension, headache, and muscle ache) in a single dialysis center by demonstrated that when dialysate had bacterial counts lower than 10 2 CFU/ml, there was a 4% attack rate; however, when concentrations exceeded 10 4 CFU/ml, the attack rate for pyrogenic reactions increased to 24% (36). Additional studies and outbreak investigations demonstrated that the incoming water and final dialysis fluids should not exceed a maximum contaminant level (MCL) of 100-1000 CFU because of possible pyrogenic or septicemic complications (37,38). The limits were established by consensus as 2000 CFU/ml for the dialysate bath and one log 10 lower for water used to prepare the dialysate as a result of these findings.…”
Section: Microbial Standards and Methodsmentioning
confidence: 99%
“…Critical evaluation of methods for isolation or quantitation of gram-negative bacterial pathogens has been hampered to some degree by the obvious requirement of simulating their characteristics in natural ecological niches in the laboratory environment. That physiological changes do occur upon introduction into these artificial systems has been strikingly demonstrated in studies showing altered responses of laboratory subcultured organisms to various types of disinfectants (3,5,11) and differences in growth characteristics (6,10).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, such techniques typically require the use of physical or chemical agents (11,16,17,18,20,23,25) either to inhibit substantial fractions of the total microbial flora or to enhance the growth or development of distin-guishing characteristics that enable rapid detection of specific organisms. Whether the restrictions imposed by the use of selective media, on which injured or stressed populations may be unable to recover, further compounds the problems of interpreting results obtained in in vitro environments has been questioned by Hoadley and Cheng (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the AAMI standards for water and dialysate quality were first being developed in the late 1970s, the batch dialysate systems in common use during the 1960s and early 1970s were known to provide an excellent environment for bacterial proliferation (5,6). Further, clinical data showed an association between the number of bacteria in the dialysate and the occurrence of pyrogenic reactions (7,8).…”
Section: Historical Contextmentioning
confidence: 99%